2016
DOI: 10.1007/s13592-015-0424-4
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of the neonicotinoid thiamethoxam during the larval stage affects the survival and development of the stingless bee, Scaptotrigona aff. depilis

Abstract: -In Brazil, where the use of neonicotinoids is allowed in bee-attracting flowering crops, we investigated whether thiamethoxam intake during the larval stage of the native bee species Scaptotrigona aff. depilis affects the survival and development by exposing larvae to contaminated food. Our results indicated that the larvae exposed to the dose at a field-realistic level and to the doses ranging around it had their survival rates significantly impaired. At the highest doses, we observed larvae and pupae with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 48 publications
1
22
0
2
Order By: Relevance
“…Lourenco et al (2012) found that for fipronil topical LD50 (0.6 ng/bee 48 h) and oral LC50 (0.011 ng/μL 48 h) were also lower than that of the honeybee. Rosa et al (2016) found decreased larval survival feeding field-realistic doses (0.004 to 4.375 ng/larva) of thiamethoxam to Scaptotrigona depilis larvae in vitro. Low doses of fipronil (0.27 ng/bee topical, 0.24 ng/bee oral) affected brain morphology by apoptosis or necrosis of mushroom bodies of Scaptotrigona postica (Jacob et al 2015), comparable to its effect on mushroom bodies of A. mellifera (Roat et al 2014).…”
Section: Other Pollinatorsmentioning
confidence: 81%
“…Lourenco et al (2012) found that for fipronil topical LD50 (0.6 ng/bee 48 h) and oral LC50 (0.011 ng/μL 48 h) were also lower than that of the honeybee. Rosa et al (2016) found decreased larval survival feeding field-realistic doses (0.004 to 4.375 ng/larva) of thiamethoxam to Scaptotrigona depilis larvae in vitro. Low doses of fipronil (0.27 ng/bee topical, 0.24 ng/bee oral) affected brain morphology by apoptosis or necrosis of mushroom bodies of Scaptotrigona postica (Jacob et al 2015), comparable to its effect on mushroom bodies of A. mellifera (Roat et al 2014).…”
Section: Other Pollinatorsmentioning
confidence: 81%
“…Though underinvestigated at present, studies have shown that early exposure to neonicotinoids can negatively impact on larval development (Wu, Anelli & Sheppard, 2011; Gregorc et al, 2012; Derecka et al, 2013; Rondeau et al, 2014; Rosa et al, 2016) and may also have latent effects on adult physiology and behaviour (Yang et al, 2012; Tomé et al, 2012; Tan et al, 2015; Peng & Yang, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In the stingless bee Scaptotrigona aff. depilis thiamethoxam decreased development time in vitro from 15 to 10 days (0.044 ng/larva) or 8 days (4.375 ng/larva) while pupal development increased from 12 to 18 and 17 days, respectively [39].…”
Section: Neonicotinoids Affect Larval and Adult Developmentmentioning
confidence: 90%
“…Therefore, bees need to be protected from exposure to neonicotinoids. Many studies investigated survival after insecticide treatment targeting the cholinergic system [35][36][37][38][39][40][41][42], and numerous studies have examined their effect on brood development by registering colony constitutions of honeybees (e.g., [43][44][45]) or bumblebees (e.g., [46][47][48]). Furthermore, sub-lethal neonicotinoid effects on adult honeybees comprise disturbances of navigation and orientation [49][50][51], walking behavior [52], learning and memory [53,54], foraging behavior [55], and nurse-larva-interactions [56].…”
Section: Introductionmentioning
confidence: 99%